Tantangan dan Strategi Pendidikan Islam di Era Digital - Lailasari, Nadia (Maliki Interdisciplinary Journal, 2024)
Technological advances have brought significant changes in various aspects of life, including education, especially in the current digital era. Rapid developments in communication and information dissemination have the potential to change the way humans interact, work and learn. Important challenges include maintaining the authenticity of content, ensuring the quality of education, resolving accessibility issues, and closing the digital divide in terms of Islamic education. Nonetheless, there are ways to overcome them with the wise use of digital technology, such as developing digital literacy, expanding global access, and implementing more interactive and creative learning methods. Thus, the quality of education can be improved to help the younger generation face the challenges of the changing times, while still adhering to Islamic values. This strategy will ensure that Islamic education remains relevant in the digital age and provide the next generation with the necessary skills to deal with the dynamics of today’s evolving digital world.